Refreshing the public appetite for 'good bacteria': menus made by microbes. Issue 1 (1st January 2019) - Verran, Joanna; Redfern, James; Moravej, Haleh; Adebola, Yvonne
Abstract: A series of events was developed to engage audiences in discussion around the importance of microorganisms in the production of fermented foods, particularly through tasting. The events were designed to attract different audiences: families attending a science museum; families in their community space; and adults in different informal eating environments. Information was provided, alongside interactive activities where possible. Feedback was positive in that the audiences enjoyed the format, the food and the events themselves, although science itself was not always specifically mentioned. The dining experience format provided a versatile and informal opportunity for engagement between experts and non-experts, and is suggested as a valuable template for similar activities, assuming appropriate budgeting and advertising issues are addressed, alongside appropriate objective setting and effective evaluation.